Insight into the Structure and Activity of Surface‐Engineered Lipase Biofluids. (4th March 2019) - Zhou, Ye; Jones, Nykola C.; Nedergaard Pedersen, Jannik; Pérez, Bianca; Vrønning Hoffmann, Søren; Vang Petersen, Steen; Skov Pedersen, Jan; Perriman, Adam; Kristensen, Peter; Gao, Renjun; Guo, Zheng
Abstract: Despite a successful application of solvent‐free liquid protein (biofluids) concept to a number of commercial enzymes, the technical advantages of enzyme biofluids as hyperthermal stable biocatalysts cannot be fully utilized as up to 90–99% of native activities are lost when enzymes were made into biofluids. With a two‐step strategy (site‐directed mutagenesis and synthesis of variant biofluids) on Bacillus subtilis lipase A (BsLA), we elucidated a strong dependency of structure and activity on the number and distribution of polymer surfactant binding sites on BsLA surface. Here, it is demonstrated that improved BsLA variants can be engineered via site‐mutagenesis by a rational design, either with enhanced activity in aqueous solution in native form, or with improved physical property and increased activity in solvent‐free system in the form of a protein liquid. This work answered some fundamental questions about the surface characteristics for construction of biofluids, useful for identifying new strategies for developing advantageous biocatalysts. Abstract : Schematic illustration showing cationization of B. subtilis lipase A (BsLA) and its mutants using N, N ‐dimethyl‐1, 3‐propanediamine (DMPA) followed by electrostatic coupling of anionic polymer‐surfactant to yield a charge neutral stoichiometric conjugate [cBsLA][S]s. Blue regions on the surface of the BsLA structures show the cationic binding sites and S molecules are represented using pink tubes.